Integrating youth mental health practice nurses into general practice: effects on outpatient mental health care utilization among children and adolescents - Koet, Lukas B. M.; Verhoog, Sanne; Erdem, Özcan; Gerger, Heike; Bindels, Patrick J. E.; de Schepper, Evelien I. T.; Jansen, Wilma (European child & adolescent psychiatry, 2025)
Integration of child mental health services in general practice may improve early detection and treatment and reduce strain on specialized services. In this study we investigated whether outpatient mental health care utilization and associated costs in children and adolescents were affected by the introduction of youth mental health practice nurses (YMHPNs) in general practice. We linked healthcare data of the Rijnmond Primary Care Database to municipal registry data on child outpatient mental health care expenditures between 2019 and 2022. Using mixed models, we assessed if the presence of a YMHPN in practices was associated with outpatient mental health care utilization. Our cohort consisted of 33,971 children aged 0–17 years registered in 38 general practices in Rotterdam, the Netherlands. 5.5% of these children attended outpatient mental health services between 2019 and 2022. The proportion of children utilizing outpatient mental health care and associated costs increased over time. After correction for practice demographics and trends over time, the presence of a YMHPN in a practice was associated with small non-significant reductions in the number of children receiving outpatient care (Rate Ratio = 0.99, 95%CI 0.92 to 1.06) and associated costs (-395.80 euros 95%CI -1431.27 to 639.67) compared with practices without YMHPN. Considering the study limitations, we cautiously concluded that the introduction of YMHPNs in general practice was not associated with significant changes in outpatient mental health care utilization one to four years after implementation. Future studies should elucidate the long-term impact and underlying changes in pathways to care due to the introduction of the YMHPN.